La construcción social de los derechos y la cuestión del desarrollo : antología esencial - Calderón Gutierrez, Fernando Esteban (CLACSO, 2017)
The harshest criticism that can be leveled at our societies, institutions, and practices is that, instead of representing human voices, they prevent us from hearing them. That is why, instead of debating limited and even improbable reform projects, our first objective is to make the urgent messages that those who do not have the capacity to be heard are heard and understood.